Influence, demands, bullying and job satisfaction: a large-scale New Zealand study - Junaid, Fatima; Khandoker, Akib Mohammad; Khieu, Trang QT (New Zealand Journal of Health and Safety Practice, 2025)
This paper explores a number of factors influencing job satisfaction in the workplace. While our study aligns with existing literature on workplace influence and job demands, it specifically examines how exposure to workplace bullying affected employees’ perceived job satisfaction. Using data from a large-scale national study covering 3,612 workers in New Zealand, we analysed data from across all industries to investigate the impact of influence at work, quantitative demands and exposure to bullying on job satisfaction. Data was collected using the Copenhagen Psychosocial Questionnaire III. We conducted a series of regression models to test the relationship among study variables. The results showed that job satisfaction is influenced by all these factors. We found that those who experienced bullying had higher levels of quantitative demands and lower job satisfaction. In addition, the findings from regression analysis show that influence at work buffers the negative impact of high quantitative demands on job satisfaction.